Unveiled Femininities : Decolonizing Contemporary Art of the Antilles. (Ponti/Ponts. Langues, littératures, civilisations des pays francophone, 2025)
The choice of Julien Creuzet, a Martinican visual artist, as France’s representative at the Venice Biennale marks a significant milestone for Caribbean artists. As the first Afro-descendant to participate in this prestigious event, his presence highlights enduring tensions between the French territories and mainland France. Afro-Caribbean art, initially marginalized, has persevered through cultural syncretism. With growing interest in Antillean art, especially with Creuzet’s participation, there’s a need to acknowledge female artists’ contributions and explore how Caribbean feminine expression has evolved. Contemporary movements aim to reclaim historical traumas, including slavery and colonization, through art. This inquiry delves into how these unresolved tensions influence the portrayal of ancestral femininity. In surveying the contemporary artistic panorama of the Caribbean, we confront the existential quandary that permeates the aesthetic consciousness of a new generation of female artists. As inheritors of a fraught legacy, they grapple with the profound question of how to engage with their heritage, decolonize contemporary Caribbean art, and authentically represent ancestral femininity in today’s context.
Keywords: Antilles; contemporary art; decolonial aesthetics; women’s representation